Alveolar ridge exostoses of mandibular: A cases report - AHMED, YASER; ALAQILI, SAMAR (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Alveolar exostoses are benign, broad-based surface masses of the outer or facial aspect of the maxilla and less commonly, the mandible. They begin to develop in early adulthood and may very slowly enlarge over the years. They are painless and self-limiting, but occasionally may become several centimeters across and then contribute to periodontal disease of the adjacent teeth by forcing food during chewing in toward the teeth instead of away from them, as is normally the case. The following paper presents a very rare case of Alveolar ridge exostoses and its management with surgical exploration.Case Situation1- A female Yemeni patient aged 62 years, the chief complaint of vague facial pain extending from the angle of mandible to retromolar region since 3 months. The history of swelling on the right angle of the mandible. gradually increase the size. The exostoses was oblong in shape, measuring 1.5cm × 1cm. mucosal tissue and did not interfere with speech, chewing, or other oral functions2- A 80 year old man, He is edentulous and need to restore function and esthetic by make denture and his suffering hypertension. located in the right alveolar ridge of the mandibular at anterior region, that he firstly noticed 10 years earlier. Its dimensions constant over time. The mass appeared nodular, pink and white. It was no mobile, anchored to the gingiva and not pain when palpated.Conclusion:1- The exostoses of the jaws in Yemen are rarity because the Congenital disorder of jaws are not common.2- The cusses of Alveolar exostoses a traumatic or traumatic extraction and not occurring by Hypertension.3- Remove the bony exostoses for good retention and stabile of the denture.